2019
DOI: 10.1108/ijilt-11-2018-0131
|View full text |Cite
|
Sign up to set email alerts
|

Redesigning initial teacher’s education practices with learning scenarios

Abstract: Purpose The construction of learning scenarios is a way to plan for teaching activities, promoting the development of skills related to problem solving, collaboration, critical thinking and creativity. Using learning scenarios as a lesson planning strategy becomes a powerful tool in initial teacher education. On the one hand, it mobilizes teaching-related scientific concepts, and on the other hand, it offers opportunities to think on innovative pedagogic approaches involving strategies and capacities essential… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
42
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(45 citation statements)
references
References 28 publications
0
42
0
3
Order By: Relevance
“…Authors of several studies have reported a low level of PDC among teacher educators and that the use of digital technology in TE is not sufficiently developed in preparatory programmes for teaching in K-12 schools (Krumsvik, 2014;Pedro, Piedade, Matos, & Pedro, 2019;Tondeur et al, 2019). For example, Hanell (2018) pointed out that local authorities in Sweden see a major challenge in the unsatisfactorily low level of PDC among newly qualified teachers, whereas Krumsvik (2014) concluded that informed educational use of digital technology in today's TE requires teacher educators with high PDC levels.…”
Section: Previous Research Teacher Educators' Professional Digital Comentioning
confidence: 99%
See 1 more Smart Citation
“…Authors of several studies have reported a low level of PDC among teacher educators and that the use of digital technology in TE is not sufficiently developed in preparatory programmes for teaching in K-12 schools (Krumsvik, 2014;Pedro, Piedade, Matos, & Pedro, 2019;Tondeur et al, 2019). For example, Hanell (2018) pointed out that local authorities in Sweden see a major challenge in the unsatisfactorily low level of PDC among newly qualified teachers, whereas Krumsvik (2014) concluded that informed educational use of digital technology in today's TE requires teacher educators with high PDC levels.…”
Section: Previous Research Teacher Educators' Professional Digital Comentioning
confidence: 99%
“…Similarly, Foulgeri, Graziano, Schmidt-Crawford, and Slukhuis (2017) suggested that TPACK can make the important PDC components for student teachers to develop during TE visible for teacher educators, so that they can teach in a technology-efficient way. Furthermore, Pedro et al (2019) argued that student teachers having contact with practice schools equipped with digital technology will increase the quality of preparations aimed at enhancing their PDC. Krumsvik (2011) pointed out a need for teacher educators to have a professional development framework that supports professional competence in using digital tools.…”
Section: Possibilities For Student Teachers To Develop Professional Dmentioning
confidence: 99%
“…Despite the limitations, a set of relevant results were systematized about how pre-service teachers put the aspects of the theory they have learned in the preparation of the learning scenarios with robotics into practice. The design of learning scenarios, supported in active learning approaches, is a regular practice in pre-service teacher education at the University of Lisbon [31,32]. For Tetchueng, Garlatti, and Laube [33], learning scenarios are a powerful tool to plan and describe learning activities to acquire knowledge domains and know-how to solve particular problems.…”
Section: Implications For Pre-service Teacher Educationmentioning
confidence: 99%
“…Este conceito tem sido utilizado em diferentes áreas de atividade como estratégia para projetar o futuro, antecipando problemas e prevendo soluções para esses mesmos problemas. A utilização de cenários em situações de educação e formação apela ao desenvolvimento da capacidade de imaginar de forma fundamentada e sustentada situações educativas com objetivos claros e específicos (Pedro, Piedade & Matos, 2019). Identifica-se por isso uma relação natural entre essa capacidade e competências relacionadas com o pensamento crítico e criativo, a resolução de problemas, a comunicação e a colaboração, competências estas que têm vindo a ser recorrentemente referidas em vários referenciais internacionais (Pedro & Matos, 2019).…”
Section: O Papel Estratégico Dos Cenários De Aprendizagemunclassified
“…Características de um cenário de aprendizagem (Matos, 2014) O processo de desenho e implementação de um CdA é condicionado por diversos fatores inerentes ao processo educativo, desde a área disciplinar e o domínio do conhecimento, passando pelos papéis dos diferentes intervenientes (e.g. alunos, professores, especialistas, convidados) até às sequências das atividades e tarefas de aprendizagem (Pedro et al, 2019). Sistematizando este processo, Matos (2014) definiu um conjunto de seis princípios orientadores que devem estar na base no processo de desenho de cenários de aprendizagem:…”
Section: O Papel Estratégico Dos Cenários De Aprendizagemunclassified